MARKETING DE RELACIONAMENTO NAS INSTITUIÇÕES DE ENSINO SUPERIOR: Estudo de caso da Universidade Metodista de São Paulo e da Universidade Metodista de Piracicaba - Garcia, Paulo Roberto Salles (2011)
Relationship marketing as a tool to attract and retain students of private higher education is the theme of this research. This is a multiple embedded case study focusing on the Methodist University of São Paulo (UMESP) and Methodist University of Piracicaba (UNIMEP) which has as main objectives to point to factors that motivate students to choose certain higher education institutions, identifying how they act on the task of attracting them aiming to establish a relationship and effective communication with these stakeholders and keep them, as well as assessing the actual effectiveness of actions taken by the institutions. It proposes a theoretical incursion to address psychological motivations, cultural, economic and social issues related to the act of consuming and establish a correlation with the consumer-student . It also discusses characteristics of relationship marketing linked to the educational context and points to difficulties/challenges experienced by educational institutions in efforts to create and strengthen ties with students in order to make such a lasting partnership. 1400 questionnaires were administered at both universities to identify, among other things, desirableattributes of a high education institution, influencing factors for abandoning it and characteristics associated with communication processes that represent differential points. The study shows that despite the financial problems are a complicating component to the attraction and retention of students, others are also crucial, as the level of teaching excellence, faculty and the quality of the relationship established by educational institutions with such public. This quality, necessarily, is linked to attributes such as freedom to express ideas, space for dialogue and open communication, elements that challenge the current educational model and encourage to criate a new one.